The Short-Term Effect of Stent Size and Number on Left Ventricular Systolic Function Improvement After Elective Percutaneous Coronary Intervention - Sh. Mostafa; O. Sanad; M. Shawky; M. Magdy; E. Elkeshk (Столичная издательская компания, 2020)
Background. The effect of stent size and number on left ventricular systolic function improvement after percutaneous coronary intervention (PCI) using drug eluting stent is not clear enough.Aim. To study short-term effect of stent size and number on left ventricular systolic function improvement after elective PCI.Material and methods. The study included 150 adult patients with electively stented left anterior descending artery lesion with drug-eluting stent. Patients were examined before PCI and 1 and 3 months after PCI using speckle tracking echocardiography.Results. Before revascularization, mean left ventricular ejection fraction was 51.2%±5.7, mean global longitudinal peak systolic strain (GLPSS) --9.29±0.94%. One month after PCI, mean GLPSS improved significantly to -14.05±1.72% (p<0.001), 3 months after PCI, even more significant improvement in the GLPSS up to -18.61±3.02% (p<0.001) was recorded. After 3 months, 53 patients (35.3%) showed recovery to normal GLPSS. The predictors of non-improvement of GLPSS after 3 months were: diabetes mellitus (p=0.007), smoking (p=0.01), dyslipidemia (p=0.001), stent length (p=0.001), and a number of stents (p=0.04). There was strong negative correlation between stent length and improvement of the GLPSS in 1 month (p=0.007) and in 3 months (p<0.001). Also there was strong negative correlation between number of stents and improvement in 1 month (p=0.002) and in 3 months (p=0.004), but the correlation between stent diameter and improvement of the GLPSS was significant neither in 1 month nor in 3 months (p=0.924 and p=0.435, respectively).Conclusion. Number and length of stents implanted were predictors to improvement of systolic function, while stent diameter doesn't affect left ventricular recovery.